Self-adaptation for robustness and cooperation in holonic multi-agent systems - Leitão, Paulo (2010)
This paper reflects a discussion at the SARC workshop, held in Venice, October 2008. This workshop addresses robustness and cooperation in holonic multi-agent systems within a context of self-organizing and selfadaptive systems. The paper first presents the basic principles underlying holonic systems. The holonic system reveals itself as a ‘law of the artificial’: in a demanding and dynamic environment, all the larger systems will be holonic. Next, it addresses robustness in holonic systems, including its relationship to self-organization and self-adaptation. These self-* systems indeed are capable of delivering superior robustness. Third, it addresses cooperation in holons and holonic systems, including its relationship with the autonomy of the individual holons. Cooperation imposes constraints on a holon such that its chances of survival and success increase.